Künstliche Intelligenz und Gefährdungshaftung im öffentlichen Recht Zur Notwendigkeit der Einführung eines speziellen Gefährdungshaftungstatbestands - Pauli, Laura Katharina (Internetrecht und Digitale Gesellschaft (IDG), 2023)
»Artificial Intelligence and Strict Liability in Public Law. On the Necessity of Introducing a Special Endangering Liability Statute«: Due to its learning ability and intransparency, the use of AI entails particular risks. In this respect, the question of whether the state may use AI vis-à-vis citizens depends crucially on the scope of liability at the secondary level. The current state liability law does not provide sufficient secondary legal protection. Instead, there is a need for the introduction of a public-law strict liability statute that provides adequate compensation for the AI-specific risks.